Drug Delivery Vectors: Neoadjuvant Chemotherapy Based on Abraxane/Human Neutrophils Cytopharmaceuticals with Radiotherapy for Gastric Cancer (Small 5/2019). Issue 5 (1st February 2019) - Ju, Caoyun; Wen, Yajing; Zhang, Luping; Wang, Qianqian; Xue, Lingjing; Shen, Jian; Zhang, Can
Abstract : Kuafu Chasing the Sun is a famous mythology story in China. Kuafu wished to capture the sun and he never ever gave up on that goal. In article number1804191, Can Zhang and co‐workers use human neutrophils cyto‐pharmaceuticals to chase radiation just as Kuafu runs after the sun, to achieve the collaborative treatment of gastric cancer.